Comparative study on the microbiological quality of vegetables collected from local markets and super shops of Dhaka city (Stamford Journal of Microbiology, 2021)
Vegetables are major source of vitamins and fibers but presence of pathogens in salad vegetables can cause outbreak of diseases. Several studies have been conducted on commonly consumed vegetables so far to detect the level of microbial contamination. However, few of them compare the microbial quality of local and super shop vegetables. The present study was conducted for microbiological assessment and comparing four types of vegetables collected from two different market conditions. In this study, Green chili (Capsicum frutescens L.), Tomato (Solanum lycopersicum), Coriander (Coriandrum sativum) and Lady’s finger (Abelmoschus esculentus) were analyzed to determine Total Viable Bacterial (TVB) Counts, Total Fungal (TF) Counts, Total Coliform Counts (TCC), Total Fecal Coliform (TFC) Counts and occurrence of Staphylococcus aureus, Pseudomonas spp., Listeria spp., Bacillus spp., Salmonella spp., and Vibrio spp. Among these microorganisms, Klebsiella spp. and Pseudomonas spp. were significantly present in coriander of both local market and super shop. All pathogenic bacteria and fungi were found in huge amounts in the vegetable samples of the local market. Although some pathogenic bacteria and fungi were also found in the same samples of the super shop, relatively lower than the local market’s vegetables. In conclusion, contamination in collected vegetable samples were not acceptable but comparatively higher load in local market samples indicated that the hygienic condition in these markets is not sufficiently maintained.Stamford Journal of Microbiology, Vol.11 (1) 2021: 24-27